2013
DOI: 10.3892/mmr.2013.1351
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of C10orf116 promotes proliferation, inhibits apoptosis and enhances glucose transport in 3T3-L1 adipocytes

Abstract: Abstract. Data from our previous study demonstrated thatC10orf116 is an adipocyte lineage-specific nuclear factor, which regulates master adipogenesis transcription factors during early differentiation. However, the precise functional properties of this gene have yet to be identified and further investigation is required. In the present study, we report the effects of C10orf116 expression on cell proliferation and apoptosis in vitro and observed that the overexpression of C10orf116 stimulates proliferation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, the expression for several genes, such as GDF10 , C10orf116 , GCOM1 , GART , WDR46 , SLC25A10 and PECAM1 were population specific, in which C10orf116 [24], GART [25] and SLC25A10 [26] had been reported to be functional in metabolic processes. These results were consistent with the previous findings that Asians and Caucasians had significantly different metabolic profiles [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the expression for several genes, such as GDF10 , C10orf116 , GCOM1 , GART , WDR46 , SLC25A10 and PECAM1 were population specific, in which C10orf116 [24], GART [25] and SLC25A10 [26] had been reported to be functional in metabolic processes. These results were consistent with the previous findings that Asians and Caucasians had significantly different metabolic profiles [27].…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that for lung adenocarcinoma patients from both Asian and Caucasian cohort studies, the apoptosis pathway might be turned down and cell-cycle pathway might be powered up. Also, we observed that metabolic genes including C10orf116 [24], GART [25] and SLC25A10 were differentially expressed between Caucasian and Asian populations. However, additional studies are required to validate that these discrepancies are population-specific and not due to technical variation.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of ADIRF has been shown to increase the transcription of C/EBPα and PPARγ to facilitate adipogenic differentiation. Overexpression of ADIRF also promotes cell proliferation and inhibits apoptosis ( Chen et al, 2013 ). Most of these mRNAs we screened out are involved in cytoskeletal changes, which have been proven to be closely linked to MSC differentiation ( Viale-Bouroncle et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most downregulated gene in [S] was the uncharacterized C10orf116 (−6·0-fold) followed by GPAM (glycerol-3-phosphate acyltransferase, mitochondrial) at −5·2-fold. C10orf116, also known as Adipose most abundant gene transcript 2 (APM2), is known to be expressed in adipose tissue and over expression of the encoded protein leads to increased cellular proliferation and increased glucose transport but its full functional significance, particularly in the liver, is unknown (Chen et al 2013). GPAM, associated with many aspects of fatty acid metabolism and the synthesis of glycerolipids (Wendel et al 2009), was also downregulated in [SH] (−7·20-fold).…”
Section: Discussionmentioning
confidence: 99%